Disentangling Ultrafast Electronic and Structural Dynamics with X‐Ray Lasers. Issue 59 (24th September 2018) - Collet, Eric; Cammarata, Marco
Abstract: Directing the functionality of molecules, materials and biophysical systems is challenging both from fundamental and applied standpoints. For example, understanding the elementary processes responsible for light‐induced transformations require watching electronic and structural reorganizations on their intrinsic timescales. The X‐ray free electron lasers (X‐FEL) represent a new generation of incredibly short and ultra‐bright X‐ray source, which open new possibilities for developing the multidisciplinary field of ultrafast science. Experiments around X‐FEL provide probes, sensitive to electronic and structural reorganizations, able to monitor transformations on the femtosecond timescale (1 fs=10 −15 s). Recent years have seen terrific successes in providing a detailed view on light‐induced processes, compared to what was understood from conventional optical pump‐probe spectroscopy. This Concept article aims at illustrating, through recent studies mainly focussing on light‐induced excited spin state trapping, how these X‐FEL based techniques can help understanding light‐activated functions, by monitoring elementary electronic and structural processes that may occur beyond the Born–Oppenheimer approximation. Abstract : Light‐induced phenomena result from ultrafast and coupled electronic and structural reorganisations, which may occur beyond the Born–Oppenheimer approximation. The incredibly short and ultra‐bright X‐ray pulses delivered by X‐ray free electron lasers (X‐FEL) allow through various techniques gathering new insight into electronic and structural dynamics during light‐induced phenomena for a better understanding and control of photoactivated molecular functions.